Association between mobile technology use and child adjustment in early elementary school age - Hosokawa, Rikuya; Katsura, Toshiki (PLOS ONE, 2018)
The time that children spend using digital devices is increasing rapidly with the development of new portable and instantly accessible technology, such as smartphones and digital tablets. Although prior studies have examined the effects of traditional media on children’s development, there is limited evidence on the impact of mobile device use. The current study aimed to clarify the link between mobile device use and child adjustment. The sample included 1,642 children aged 6 in first grade at elementary schools in Japan. Parents completed a self-report questionnaire regarding their children’s use of mobile devices and emotional/behavioral adjustment. We performed inverse probability of treatment weighted (IPTW) logistic regression to compute odds ratios (OR) for emotional/behavioral problems according to mobile device use. The values for IPTW analysis were computed based on variables assessing sociodemographics and child characteristics. Among the participants, 230 (14.0%) were regular users (60 minutes or more on a typical day) and 1,412 (86.0%) non-regular users (under 60 minutes on a typical day). Relative to non-regular use, regular use of mobile devices was significantly linked to conduct problems (IPTW-OR: 1.77, 95% CI: [1.03–3.04], p < .05) and hyperactivity/inattention (IPTW-OR: 1.82, 95% CI: [1.15–2.87], p < .01). Based on these results, routine and frequent use of mobile devices appear to be associated with behavioral problems in childhood.